Collaborative action research: the ethical challenges - Janice Cook (International Journal of Evidence Based Coaching and Mentoring, 2010)
This article explores some of the ethical challenges that have been addressed primarily in the research design phase of a coaching doctoral research study. The ethical position of the researcher with a dual role of coach is examined as well as the ethical predicaments for the leaders being coached who are also collaborative researchers in this action research study. This article includes a model for developing a coaching theory from researching individual coaching practice; some important reflections from the early stages of the collaborative action research fieldwork; a model for creating a strong ethical environment for potential use by other practitioner researchers utilising action research methodology; and concludes with some key observations about the ethical challenges experienced by the researcher. The leaders participating in this research are employed in Advance, Mencap and Rethink, all UK voluntary sector organisations.